1993
DOI: 10.1246/cl.1993.343
|View full text |Cite
|
Sign up to set email alerts
|

1,2-cis-β-Mannopyranoside Formation by the Dimethylphosphinothioate Method

Abstract: 1,2-cis-β-Mannopyranosides were obtained predominantly by reactions of mannopyranosyl dimethylphosphinothioate derivatives with several alcohols in the presence of iodine and a catalytic amount of triphenylmethyl perchlorate as the activator in benzene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…For derivatives of the d -galacto series a remote effect beneficial for the formation of α-galactosides was also noted when a participating moiety was present at C-4. 43 Similar effects (including C-3 participation) were also detected for the derivatives of the l -fuco, 44 l -rhamno, 45 d -manno, 46 and d -gluco 47 series.…”
Section: Effect Of the Glycosyl Donormentioning
confidence: 52%
“…For derivatives of the d -galacto series a remote effect beneficial for the formation of α-galactosides was also noted when a participating moiety was present at C-4. 43 Similar effects (including C-3 participation) were also detected for the derivatives of the l -fuco, 44 l -rhamno, 45 d -manno, 46 and d -gluco 47 series.…”
Section: Effect Of the Glycosyl Donormentioning
confidence: 52%
“…There are several methodologies developed for the synthesis of b-mannopyranosides, 18 particularly the intramolecular aglycon delivery which tethers the glycosyl donor and the acceptor together on the same molecule. 19 Yamanoi and co-workers 20 150-162 Hz (Figure 7). 23 The interest in the preparation of S-glycosides has mainly arisen due to their increased stability towards hydrolysis by glycosidases with the premise that these may produce effective biological agents for the treatment of carcinomas and other disease states.…”
Section: Methodsmentioning
confidence: 96%
“…Glycosyl dimethylphosphinothioate donors were introduced by Inazu and co-workers in 1985, drawing inspiration from the use of this type of leaving group in peptide synthesis. , It was concluded that silver perchlorate was an efficient activator of these novel glycosyl donors, leading to disaccharides in excess of 69%, although a stoichiometric amount of the promoter was essential for the glycosylations to take place. Inazu and co-workers have since investigated dimethylphosphinothioates very thoroughly as glycosyl donors and found that iodine in combination with trityl perchlorate , was a very efficient activator for these glycosyl donors. Trityl salts such as TrClO 4 , TrBF 4 , and TrSnCl 5 have since proven to be good catalysts for the activation of the dimethylphosphinothioate donors. ,, Years after that, in 2006, Yamanoi and Inazu et al found use of the dimethylphosphinothioate leaving group in glycosylations with 1- C alkylated glycosyl donors .…”
Section: Phosphorus-based Glycosyl Donorsmentioning
confidence: 99%